MENGUNGKAP PENERAPAN STRUCTURAL CAPITAL DALAM MENCIPTAKAN DESA TANPA KEMISKINAN MELALUI PROGRAM BANTUAN DESA : DI TAMBAKREJO - Novi Dwi Yanti; Mudrifah Mudrifah (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to reveal the application of structural capital in creating villages without poverty through village assistance programs, in Tambakrejo Village. The informants in this research consist of Tambakrejo village officials and recipients of village assistance programs. Data collection techniques use interview and observation techniques. Research methods are used. used is qualitative with the data source in the form of primary data. The data analysis method uses the structural capital indicator framework from previous researchers. The results of this research provide evidence that the Tambakrejo Village Government has implemented structural capital indicators consisting of structure, process, objectives, culture, planning, management and expenditure of financial resources, information systems, and the availability of direction in obtaining information